IMPLICATIONS OF INFORMATION TECHNOLOGY ON PERFORMANCE OF BUSINESS MANAGEMENT THROUGH A REMOTE AUDIT APPROACH TO AUDIT QUALITY - Harsanto Harsanto; Kumaratih Sandradewi; Andriani Kusumaningrum; Afu Ichsan Pradana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The company, in the face of the prolonged Covid-19 pandemic, which has entered its third year, has made many changes and changes from various sides. These changes and changes have brought a lot of acceleration in technological progress and exploration, this is part of the company's adaptive response. In response to the prolonged Covid-19 pandemic , business management and performance quality monitoring have become a means of strengthening the business wheel, so that it becomes a relevant link, those responsible for business management governance are required to compile and present financial reports along with other relevant disclosures based on the best judgment and analysis of current facts and predictable events after the reporting date. Starting from efforts to strengthen business management performance while the Covid-19 pandemic situation requires the fulfillment of health protocols and social distancing policies , the supervisory department and audit system in business organizations are faced with a dilemma of interest, namely between maintaining audit quality and being able to obtain sufficient and appropriate audit evidence. to support the audit opinion through modifying audit evidence collection procedures, revising the process for identifying and assessing risks of material misstatement, and changing planned audit procedures or performing alternative or follow-up audit procedures as appropriate. Exploration of information technology and investment in technology that will provide a solution to facilitate communication between the auditor department and business management using remote audit potential or known as remote audit , so that with this alternative solution the performance of business management can be optimized for monitoring and escorting the wheels of business by exploring deeper into the use of remote audit in influencing audit quality. Keywords: Covid-19 pandemic, remote audit , audit software , information technology, management performance